Adsorptive Removal of Phosphate from Aqueous Solutions using Ceria-Titania Mixed Oxide - Satapathy, P.K.; Behera, R.K.; Nayak, A.K.; Mishra, T. (Asian Journal of Chemistry, 2011)
The present study is an attempt to use ceria-titania mixed oxide as an adsorbent for removal of phosphate from aqueous solution. Physico-chemical characterization revealed that ceria-titania mixed oxide has anatase phase indicating the homogeneous distribution of cerium in the anatase crystal lattice without forming any separate cerium oxide phase. Pore size distribution study indicated the mesoporous nature of the material. The adsorption studies were carried out with respect to effect of pH, initial phosphate concentration and amount of adsorbent. Phosphate uptake was seen to increase with increasing amount of adsorbent and pH and attains maximum at pH 5.0 whereas it decreases with increasing concentration of phosphate solution. The experimental equilibrium adsorption data were fitted with Langmuir isotherm indicating monolayer adsorption.